2022
DOI: 10.1111/1745-9125.12303
|View full text |Cite
|
Sign up to set email alerts
|

Social order and social justice: Moral intuitions, systemic racism beliefs, and Americans’ divergent attitudes toward Black Lives Matter and police

Abstract: We examine the influence of moral intuitions on Americans’ divergent attitudes toward Black Lives Matter (BLM) and police. Drawing on Moral Foundations Theory, we hypothesize that individualizing moral intuitions that put care and protection of the vulnerable at the center of moral concern (a social justice orientation) lead people to express positive feelings toward BLM and negative feelings toward police, whereas binding moral intuitions that put social stability at the center of moral concern (a social orde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
39
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(48 citation statements)
references
References 71 publications
4
39
0
Order By: Relevance
“…Furthermore, the current investigation found weak evidence of a suspect race effect on evaluations of use of force, which shows promise for mock jurors’ ability to disregard this extralegal factor in a civil liability context. However, consistent with prior work showing the impact of evaluators’ individual differences on judgments of police and use of force (Drakulich et al., 2020; Reynolds et al., 2018; Silver et al., 2022), this research did reveal a robust influence of mock jurors’ attitudes toward police legitimacy and feelings toward BLM. Together, these results begin to catalogue the factors that drive judgments and decisions when people apply the reasonable officer standard in civil cases involving officer use of force.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Furthermore, the current investigation found weak evidence of a suspect race effect on evaluations of use of force, which shows promise for mock jurors’ ability to disregard this extralegal factor in a civil liability context. However, consistent with prior work showing the impact of evaluators’ individual differences on judgments of police and use of force (Drakulich et al., 2020; Reynolds et al., 2018; Silver et al., 2022), this research did reveal a robust influence of mock jurors’ attitudes toward police legitimacy and feelings toward BLM. Together, these results begin to catalogue the factors that drive judgments and decisions when people apply the reasonable officer standard in civil cases involving officer use of force.…”
Section: Discussionsupporting
confidence: 87%
“…Recent studies examining sentiments toward both policing and BLM suggest an inverse relationship between these factors, if only indirectly. For instance, Silver et al (2022) demonstrated that moral intuitions and beliefs about systematic racism inversely predicted warmth toward the police and warmth toward BLM. Furthermore, Metcalfe and Pickett (2022) found that increased support for BLM predicted decreased support of various tactics for policing protests, including using less-than-lethal force to control protestors.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The protest movement of Occupy the Wall Street in 2011 was small in scale and neither political parties attempted to stir it up for their own political gain. Studies have been done on "Occupy DC" and "Occupy Wall Stree" participants (Maguire et al, 2018;Tyler et al, 2018), and from contestants of the Balck Lives Matter movement (Metcalfe & Pickett, 2022;Silver et al, 2022), but not from the viewpoint of the general public. Using survey data from Taiwan, this article attempts to examine how the public at large perceived police behavior during a political crisis.…”
Section: Theory and Literature Reviewmentioning
confidence: 99%
“…We attempt to fill in the research gap in the studies of police legitimacy by examining to what extent police action could continue to garner public support under a political crisis. Previous researchers (Maguire et al, 2018;Metcalfe & Pickett, 2022;Silver et al, 2022;Tyler et al, 2018) have only examined the reaction to the police from protest participants' point of view. We rely on a variant of measure of perceived police legitimacy, containing items of both procedural justice and police effectiveness, and test whether this measure is related to the support for the police during the political crisis.…”
mentioning
confidence: 99%